GAMBARAN KESEJAHTERAAN SISWA SEKOLAH MENENGAH DI JAKARTA: STUDI SELAMA PANDEMI COVID-19 - Rahmah Hastuti; Pamela Hendra Heng; Naomi Soetikno (PROSIDING SERINA, 2021)
This study aims to examine empirically related to the conception of subjective well-being of high school students in Jakarta during the Covid-19 pandemic situation, through a quantitative survey. Measurement were carried out through testing the aspects contains in the subjective well-being as a meaning of evaluation from the student perspective. Data collection was carried out from November until early December 2020. The research instruments includer: informed consent, a questionnaire on the Satisfaction with Life Questionnaire (SWLS) developed by Diener, in the e-questionnaire form. Data collection was done by using convenience sampling technique. This type of sampling is a non-probability sampling. Based on the results on 107 high school students in Jakarta, the majority of whom are women (54.2%) than men. Students are in the range of 15 to 19 year, the majority are 16 years old (35.5%). From the results data processing, it was found that there were differences in student’s subjective well-being in terms of the sex of participants. Through this research findings show that students perceive about subjective well-being tends to be high (57.9%). However, based on the analysis with multiple responses that their subjective well-being during the pandemic were varied, some were negative, positive and neutral. The implication of this research, especially on family psychology, is that a meaningful relationship or quality is needed between the teenager and parents. High school student was in the adolescent stage, during the pandemic Covid-19 were feel boredom, sadness because they cannot interact with friends at school and they perceive that there are so many difficulties during school from home, but in the other hands their feel closer to their family.